A Summary of Recommendations for Plastic Surgeons during the Coronavirus Disease 2019 Outbreak. Issue 7 (July 2020) - Schoenbrunner, Anna R.; Sarac, Benjamin A.; Janis, Jeffrey E.
Abstract : Background: The coronavirus disease 2019 outbreak presents unique challenges to the healthcare system. The lack of unified guidelines on what constitutes elective surgery left plastic surgeons without a clear framework to guide their practices. More urgently, the ambiguity in defining elective surgery leaves plastic surgeons without clear guidance as states begin to phase in these procedures. Methods: Recommendations issued by state governing bodies as of April 28, 2020, were reviewed. National society and federal guidelines pertaining to postponement and resumption of elective surgeries affected by the coronavirus disease 2019 outbreak were also reviewed. Recommendations based on the above are collated for plastic surgeons. Results: Thirty-six states and the District of Columbia provide recommendations regarding elective surgery. Cosmetic surgery is considered an elective surgery and should be postponed; this may be among the first elective surgeries to safely resume. Societal guidelines provide disease-specific recommendations for cancer-related surgery and breast reconstruction. Trauma, other cancer-related reconstruction, and hand surgeries are considered nonelective if postponement threatens life or limb or if a patient is highly symptomatic. Postponement and resumption of oncology, trauma, and hand surgery cases depend on disease stage and complexity of reconstruction. Pediatric craniofacial surgery presents unique challenges due to the time-sensitive nature of the interventions. Conclusions: Guidance on elective surgery is vague for plastic surgeons. Government recommendations and societal guidelines provide a framework for plastic surgeons to assess the elective nature of a surgical intervention and safety of resumption; however, a nuanced assessment must be made on local disease transmission, supply availability, and hospital capacity. Abstract : Supplemental Digital Content is available in the text.